MicroRNAs: Mediators and Therapeutic Targets to Airway Hyper Reactivity After Respiratory Syncytial Virus Infection - Feng, Shuwen; Zeng, Dongxin; Zheng, Junwen; Zhao, Dongchi (Frontiers in Microbiology, 2018)
Respiratory syncytial virus (RSV) is the most important pathogen correlated to the first-time infant wheezing and later recurrence after its primary infection. RSV infection promotes the bronchial smooth muscle sensitivity to leukotrienes (LTs) in acute stage, causes the extensive inflammatory reaction and the aggregation of Th2-like cells during respiratory tract obstruction. Infants and young children infected with RSV exhibit an increased susceptibility to the exposure of exogenous allergens, easy to suffer from the recurrent wheezing, which prompts that the body is still in a state of inflammation or immunological bias. However, the pathological mechanism is unclear. The recent researches demonstrate that abnormal expression of non-coding microRNAs (miRNAs) can be detected from the peripheral blood and airway tract epithelial of RSV infected infants, which participate the regulation of immune cells polarization and LTs synthesis. Improving the immune tolerance can significantly relieve the airway inflammation and broncho-spasm caused by RSV. In this review, we discuss recent advances in understanding the mechanism of RSV-induced inflammatory reaction and immune dysfunction leading to airway hyper-reactivity. Further, we summarize the potential molecular basis that, in this process, miRNAs, which are produced by airway epithelial cells or peripheral blood mononuclear cells, directly or in the form of exosome to regulate the inflammation programs as well as the function, differentiation and proliferation of immune cells. miRNAs may become a potential bio-marker of detecting severe RSV infection and a novel target of early intervention and therapeutic strategy in recurrent wheezing or asthma related to RSV infection.